The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/mcp.m112.023135
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution and Neofunctionalization of Snake Venom Metalloprotease Domains

Abstract: Snake venom metalloproteases (SVMP) are composed of five domains: signal peptide, propeptide, metalloprotease, disintegrin, and cysteine-rich. Secreted toxins are typically combinatorial variations of the latter three domains. The SVMP-encoding genes of Psammophis mossambicus venom are unique in containing only the signal and propeptide domains. We show that the Psammophis SVMP propeptide evolves rapidly and is subject to a high degree of positive selection. Unlike Psammophis, some species of Echis express bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 68 publications
3
63
0
3
Order By: Relevance
“…All of the SVMP contigs we identified were members of the P-III class, which is unsurprising considering that P-II and P-I SVMPs have only previously been detected from viperid snakes [43], [44]. It is worth noting that we did not find any evidence of any atypical truncated SVMPs such as those previously described from the non-front-fanged snake Psammophis mossambicus (family Lamprophiidae) [45]. Phylogenetic analysis of boomslang SVMPs with representative orthologs from other taxa revealed that all but one of the boomslang SVMPs group together in a clade sister to that containing SVMPs from the xenodontid snake Philodryas olfersii , the atractaspid Atractaspis microlepidotus and various elapid snakes (Fig.…”
Section: Resultssupporting
confidence: 62%
“…All of the SVMP contigs we identified were members of the P-III class, which is unsurprising considering that P-II and P-I SVMPs have only previously been detected from viperid snakes [43], [44]. It is worth noting that we did not find any evidence of any atypical truncated SVMPs such as those previously described from the non-front-fanged snake Psammophis mossambicus (family Lamprophiidae) [45]. Phylogenetic analysis of boomslang SVMPs with representative orthologs from other taxa revealed that all but one of the boomslang SVMPs group together in a clade sister to that containing SVMPs from the xenodontid snake Philodryas olfersii , the atractaspid Atractaspis microlepidotus and various elapid snakes (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Acute pain through ASIC1 activation (Bohlen et al, 2011) Inflammatory pain, thermal hypersalgesia and mechanical allodynia (Zhang et al, 2017) Excitation of sensory neurons (Bohlen et al, 2011;Zhang et al, 2017) Neurogenic inflammation (Camara et al, 2003;Camargo et al, 2008) Non-neurogenic inflammation Endematogenic and pro-inflammatory (Camara et al, 2003;Casais-E-Silva et al, 2016;Costa et al, 2017) Inhibits platelet aggregation (Teixeira et al, 2011) Phospholipase activity (Gutierrez and Ownby, 2003) Myotoxic (Harris and Maltin, 1982) Pre-synaptic toxin, block of neuromuscular transmission leading to muscle paralysis (Sribar et al, 2014;Gutierrez et al, 2017) SVMP Inflammatory hyperalgesia (Fernandes et al, 2007;Bernardes et al, 2015;De Toni et al, 2015;Ferraz et al, 2015) Endematogenic activity independent of pro-inflammatory mediators (Laing et al, 2003) Cleavage of basement membrane of capillary vessels and endothelial cells adhesion proteins (Gutierrez et al, 2005;Escalante et al, 2011) Procoagulant through activation of prothrombin and Factor X (Takeda et al, 2012;Ainsworth et al, 2018) Inhibition of platelet aggregation (Kamiguti, 2005) Dermonecrotic activity dependent on TNF signaling (Laing et al, 2003) Potential paralysis through inhibition of α-7 neuronal AChR by the cysteine-rich and disintregin-like domains complex (Brust et al, 2013) SVSP Mild mechanical hyperalgesia (Menaldo et al, 2013) Leucocyte migration (Menaldo et al, 2013) Mild edema (Zychar et al, 2010) Procoagulant through activation of prothrombin and factors VII and X (Kini, 2005) Anti-coagulant through activation of Prot...…”
Section: Pla2smentioning
confidence: 99%
“…They have also been used in recent years for the discovery, isolation and characterisation of bioactive peptides from snakes, spiders and cone snails. [134][135][136] Due to the ubiquitous nature of the Ca 2+ signal, the large Ca 2+ gradient across cell membranes and superior spectrophotometric properties of Ca 2+ dyes, 137 high-throughput Ca 2+ assays are particularly attractive for isolating, identifying and characterising venom components with activity at a range of voltage-and ligand-gated ion channels (e.g. TRP channels and nAChRs) and GPCRs.…”
Section: Fluorescence-based Assaysmentioning
confidence: 99%